A New Posterior Semi-Fixed Temporary Bite Raising Appliance - Chachada, Achint; Pedgaonkar, Sneha (Orthodontic Journal of Nepal, 2020)
In clinical scenarios like anterior cross bite and Angle’s Class II division 2 malocclusion, it is often required to raise the bite temporarily for an effective unobstructed tooth movement of maxillary/mandibular incisors. For relieving the occlusion, numerous removable acrylic plates with bite blocks, glass ionomer splints or fixed bite blocks are commonly used. But each of these are having certain disadvantages. This technique describes semi-fixed posterior acrylic bite blocks which are fixed using “T” shaped spring to the vertically oriented lingual sheaths welded on molar bands both buccally and lingually for added retention. This technique has been found to be reliable and convenient, especially since it allows easy insertion and removal by the orthodontist and avoids the loosening of the bite block before patient’s next visit and keeps the bite open as desired.